Positive Clinical Neuroscience: Explorations in Positive Neurology. (August 2013) - Kapur, Narinder; Cole, Jonathan; Manly, Tom; Viskontas, Indre; Ninteman, Aafke; Hasher, Lynn; Pascual-Leone, Alvaro
Disorders of the brain and its sensory organs have traditionally been associated with deficits in movement, perception, cognition, emotion, and behavior. It is increasingly evident, however, that positive phenomena may also occur in such conditions, with implications for the individual, science, medicine, and for society. This article provides a selective review of such positive phenomena – enhanced function after brain lesions, better-than-normal performance in people with sensory loss, creativity associated with neurological disease, and enhanced performance associated with aging. We propose that, akin to the well-established field of positive psychology and the emerging field of positive clinical psychology, the nascent fields of positive neurology and positive neuropsychology offer new avenues to understand brain-behavior relationships, with both theoretical and therapeutic implications.